The geomorphological and sedimentological legacy of the historical Lake Lorsch within the Weschnitz floodplain (northeastern Upper Rhine Graben, Germany) - Henselowsky, Felix; Fischer, Peter; Appel, Elena; Jäger, Barbara; Hillmus, Nicolai; Sandbrink, Helen; Becker, Thomas; Prien, Roland; Schenk, Gerrit Jasper; Mächtle, Bertil; Recker, Udo; Bubenzer, Olaf; et al. (Quaternary science journal, 2026)
The artificial historical Lake Lorsch (1474/1479 to 1718/1720 CE) in the northeastern Upper Rhine Graben (Germany) is known from various historical sources (e.g., for fish farming) as a significant anthropogenic imprint of the Weschnitz floodplain. Nevertheless, there have been no geomorphological and sedimentological investigations into the (quasi-)natural context for the creation of the lake, its importance as a potential sediment archive and the subsequent use of the lake area until modern times. No relics of the lake can be observed in today's landscape. We investigated the geomorphological setting of the area using a high-resolution digital elevation model, groundwater-level data, and geophysical prospection, as well as sedimentological information from four sediment cores. Results indicate that the location of the lake is topographically deeper in relation to its receiving waters of the old Weschnitz and that Lake Lorsch was fed by groundwater. Sedimentary analysis (core LOR 21A, unit 2; LOSE 4 and LOSE 5, unit 3) exhibits lake deposit, with characteristics indicative of a limnic environment and a high groundwater table. At the same time, adjacent stratigraphy shows channel deposits (core LOR 20A, unit 3), reflecting an anthropogenically controlled inflow via a channel (Renngraben). Our results, based on a relative elevation model, fit well with the historical records: that the inflow for the anthropogenic channel was via the old Weschnitz (topographically higher than the lake area) and that the artificial Landgraben canal (topographically lower than the lake area) was crossed by a water bridge. It is a good example of how humans have acted as fluvial- and water-related agents for at least 500 years in the Weschnitz floodplain.
Gesehen am 18.02.2026